Anti-Inflammatory Effect of By-Products from Haliotis discus hannai in RAW 264.7 Cells. (12th March 2015) - Rho, Ho-Seok; Kim, Hyang; Kim, Jung-Ae; Karadeniz, Fatih; Ahn, Byul-Nim; Nam, Ki-Ho; Seo, Youngwan; Kong, Chang-Suk
Abstract : Several reports promoted the potential of shellfish due to their ability to act as antioxidant, anti-inflammatory, and antimicrobial agents. Pacific abalone, Haliotis discus hannai viscera is, reported to possess bioactivities such as antioxidative stress and anti-inflammatory. In this study, anti-inflammatory potential of mucus-secreting glands from shell-shucking waste of H. discus hannai was evaluated using RAW 264.7 mouse macrophage cell model. Results indicated that presence of H. discus hannai mucosubstance by-products (AM) significantly lowered the nitric oxide (NO) production along the expressional suppression of inflammatory mediators such as cytokines TNF- α, IL-1 β, and IL-6 and enzymes iNOS and COX-2. Also, AM was shown to increase expression of anti-inflammatory response mediator HO-1. Presence of AM also scavenged the free radicals in vitro . In conclusion, by-products of H. discus hannai are suggested to possess notable anti-inflammatory potential which promotes the possibility of utilization as functional food ingredient.